2023
DOI: 10.1021/acs.nanolett.3c01727
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Intracellular Optical Performance and Stability of Engineered Nanomaterials via Aqueous Two-Phase Purification

Aceer Nadeem,
Aidan Kindopp,
Ian Wyllie
et al.

Abstract: Supramolecular hybrids of DNA and single-walled carbon nanotubes (SWCNTs) have been introduced in numerous biosensing applications due to their unique optical properties. Recent aqueous two-phase (ATP) purification methods for SWCNTs have gained popularity by introducing specificity and homogeneity into the sensor design process. Using murine macrophages probed by near-infrared and Raman microscopies, we show that ATP purification increases the retention time of DNA-SWCNTs within cells while simultaneously enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…This supports our hypothesis that M2 and NM cells selectively internalize SWCNTs with more defects, thus having a higher defect ratio. 51 These results underline the intricate relationship between nanotube interaction and the internal cellular make-up, providing valuable insights into the nanomaterial cell dynamics. Near-infrared hyperspectral fluorescence microscopy 15 was performed on macrophage cells with internalized DNA-SWCNTs.…”
Section: Resultsmentioning
confidence: 79%
“…This supports our hypothesis that M2 and NM cells selectively internalize SWCNTs with more defects, thus having a higher defect ratio. 51 These results underline the intricate relationship between nanotube interaction and the internal cellular make-up, providing valuable insights into the nanomaterial cell dynamics. Near-infrared hyperspectral fluorescence microscopy 15 was performed on macrophage cells with internalized DNA-SWCNTs.…”
Section: Resultsmentioning
confidence: 79%
“…Jena, Roxbury, and Heller et al reported a monochiral sensor based on (GT) 6 - (8,6) nanotube that enabled detection of lipid content in endolysosomal organelles, enabling precise mapping of lipid accumulation in live cells. 110 This response mechanism 111 Results showed that ATP purification increased the retention time of DNA−SWCNTs within the cells and enhanced the intracellular optical properties. Advancement in the ATPE purification method further led to separation of a specific single-enantiomer SWCNT, presenting a notable advancement in carbon nanotechnology.…”
Section: Chirality-sorted/monochiral Swcntsmentioning
confidence: 99%
“…Nadeem and Roxbury et al used DNA–SWCNTs purified from an aqueous two-phase (ATP) extraction method to compare the intracellular fate of purified and unsorted nanotubes . Results showed that ATP purification increased the retention time of DNA–SWCNTs within the cells and enhanced the intracellular optical properties.…”
Section: Sensing With Chirality-sorted/monochiral Swcntsmentioning
confidence: 99%
“…[25][26][27] Moreover, with stable SWCNT functionalization, these sensors exhibit very promising biocompatibility. [28,29] Neurotransmitter detection has been demonstrated with a high spatial and temporal resolution for chemical mapping of cellular release processes of dopamine [17,[30][31][32] and serotonin. [26] Recent developments also show that this technology can be tailored for common microscopy equipment [33] and that extracellular dopamine can be reported in 3D by combining time-correlated single photon counting and confocal fluorescence microscopy.…”
Section: Introductionmentioning
confidence: 99%